Review Study on a Home Invading Pest Mupli Beetle (Luprops tristis) - Raju , Asha; Radhika , R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
A litter dwelling detritivore pest, Mupli beetle causes home invasions. They extend from tropical Africa, Asia to Papua New Guinea. Widely found in rubber plantation belt litter, they feed on tender rubber leaves. Huge aggregation of the beetle invasions includes 0.5 to 4 million individuals per residential building. The invasion pattern is observed after summer showers. They remain dormant in undisturbed dark corners for several months.Clusters of the beetle fall off from their hiding places in crooks and corners causing nuisance to the residents, even to move out of the buildings. Squeezing the beetle releases a phenolic secretion which causes burning on the skin. Reports also showed the onset of Keratoconjunctivitis in the regions of mupli invasions. The poor working class residing near rubber plantation areas in poorly built home facilities with leaf thatched roofs experience more problems with the beetle invasions. Attraction towards light is also another factor that might lead the beetle towards residential buildings. Natural beetle aggregation is also found common below boulders and pits near the rubber plantations.